2021
DOI: 10.1029/2021gl093029
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause Reconnection and Indents Induced by Foreshock Turbulence

Abstract: Magnetopause reconnection plays a critical role in controlling energy input from the solar wind to the magnetosphere. The possibility that magnetic fluctuations generated in the foreshock may lead to magnetopause reconnection has been considered based on observations indicating that magnetosheath fields are not a simple compression of the interplanetary magnetic field (IMF) (Russell et al., 1997;Zhang et al., 1997). On account of the fact that the statistical magnetopause locations for cone angles (between the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…The first part of this study investigated the occurrence of these magnetopause intervals downstream of either the quasi‐parallel or quasi‐perpendicular bow shock, in comparison to the general distribution of IMF orientations. While there was a statistically significant enhancement in the number of intervals observed downstream of the quasi‐parallel bow shock in comparison to the number downstream of the quasi‐perpendicular bow shock, it has not been determined that this is a result of enhanced reconnection caused by increased magnetosheath fluctuations (as has been suggested by the results of a recent hybrid simulation under nearly radial IMF with a small northward component (Chen et al., 2021)). Rather, the increased magnetosheath fluctuations downstream of the quasi‐parallel bow shock are believed to cause large scale oscillations of the magnetopause surface.…”
Section: Discussionmentioning
confidence: 94%
“…The first part of this study investigated the occurrence of these magnetopause intervals downstream of either the quasi‐parallel or quasi‐perpendicular bow shock, in comparison to the general distribution of IMF orientations. While there was a statistically significant enhancement in the number of intervals observed downstream of the quasi‐parallel bow shock in comparison to the number downstream of the quasi‐perpendicular bow shock, it has not been determined that this is a result of enhanced reconnection caused by increased magnetosheath fluctuations (as has been suggested by the results of a recent hybrid simulation under nearly radial IMF with a small northward component (Chen et al., 2021)). Rather, the increased magnetosheath fluctuations downstream of the quasi‐parallel bow shock are believed to cause large scale oscillations of the magnetopause surface.…”
Section: Discussionmentioning
confidence: 94%
“…In the simulation there are additional effects that may contribute to the transient magne- as demonstrated in 3D hybrid simulations with quasi-radial northward IMF 48 . However, for the events discussed earlier, the high-speed jets are clearly important for triggering the events.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al. ( 2021 ) demonstrated that foreshock turbulence can penetrate through the magnetosheath, grow into structures of enhanced density and magnetic field, and induce reconnection. Such reconnection is localized and bursty in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pfau-Kempf et al (2020) showed that perturbations arising from kinetic instabilities in the magnetosheath can modulate the reconnection. Chen et al (2021) demonstrated that foreshock turbulence can penetrate through the magnetosheath, grow into structures of enhanced density and magnetic field, and induce reconnection. Such reconnection is localized and bursty in nature.…”
mentioning
confidence: 99%